A ministry of presence : chaplaincy, spiritual care, and the law - Sullivan, Winnifred Fallers, 1950- (University of Chicago Press, 2014)
Most people in the United States today no longer live their lives under the guidance of local institutionalized religious leadership, such as rabbis, ministers, and priests; rather, liberals and conservatives alike have taken charge of their own religious or spiritual practices. This shift, along with other social and cultural changes, has opened up a perhaps surprising space for chaplains-spiritual professionals who usually work with the endorsement of a religious community but do that work away from its immediate hierarchy, ministering in a secular institution, such as a prison, the mil.